CONTEXTUALIZATION OF ISLAMIC EDUCATION VALUES IN THE USE OF THE WORD CHICKEN IN BANJAR PROVERBS - Mubarok, Ahmad; Isnendes, Retty; Kurniawan, Eri (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: This research is motivated by the rich cultural heritage of the Banjar community and the significance of proverbs as a medium for imparting moral and educational values. Understanding the Islamic values embedded in these proverbs enhances the appreciation of local wisdom and education. Purpose: This study aims to reveal the values of Islamic education contained in the use of the chicken lexicon in the Banjar proverb and explain the function of the Banjar proverb as a medium for Islamic value education in the Banjar community. Method: The research method used is a qualitative method with a descriptive approach. Data were collected from two main books that document Banjar proverbs, namely Peribahasa Banjar Urang Banjar’ and  ‘Kamus Peribahasa Banjar’. The analysis was carried out by matching and interpreting 196 Banjar proverbs using the chicken lexicon, as well as interviews with cultural and literary sources of Banjar. Result: The results of the study show that Banjar proverbs that use the chicken lexicon contain various Islamic educational values, such as the value of faith (tawakal), sharia value (professionalism), and the value of morality (courage, compassion, humility, insight, hard work, and tolerance). Conclusion: The conclusion of this study is that the Banjar proverb with chicken lexicon is able to convey the values of Islamic education in a relevant and contextual way, strengthen cultural identity, and help shape the character of society based on Islamic teachings. The suggestion for further research is to explore more deeply the use of other animal lexicons in Banjar proverbs and their relationship to Islamic educational values.